Cosmopolitan Feminism Movement in Addressing Social Issues: A Holistic Approach of Women’s National Basketball Association (WNBA) Social Justice Council - Leolita, Dwi Asri (Sang Pencerah: Jurnal Ilmiah Universitas Muhammadiyah Buton, 2024)
This research analyzes the role of the cosmopolitan feminist movement in addressing social issues through a holistic approach with the WNBA Social Justice Council as a case study. The issue at hand is the complexity of global social challenges, raising the question of the extent to which a holistic approach is able to address these dynamics. Through an in-depth analysis of the policies, programs and activities implemented by the WNBA Social Justice Council, this research aims to identify effective strategies in responding to and addressing various social challenges. The research method uses a qualitative approach by analyzing the policies and activities of the WNBA Social Justice Council. The concepts of cosmopolitan feminism and global justice serve as theoretical frameworks to guide the exploration of cross-border solidarity in response to social issues. The research findings show that this movement successfully integrates a holistic approach through advocacy, education, and community support. In summary, this research confirms that the cosmopolitan feminist movement can effectively respond to and bring positive change in addressing social issues as a whole.